REQUIREMENTS FOR IRRIGATION WHEN IRRIGATION IS USED - Butayarov Abduqodir Tuxtayevich; Shaymanov Sharofiddin Quvondiqning o‘g‘li (European Science Publishing, 2024)
In organizing scientific research at the required level, this article introduces the need to test and implement new innovative technologies for irrigating crops in a wide range of fields. In many agricultural developed countries, a drip irrigation system has been introduced and has been recognized as a technology that provides the general public and scientifically intensive, efficient, efficient, convenient opportunities, quality and guaranteed properties. In addition to providing water from drip irrigation technology to the root layer of the plant smoothly, it provides resource opportunities. The main difference between other methods of watering is that the fields on which the crop is located are moistened uniformly.
Keywords: Irrigation, technology, technology, pool refrigerator, pump, filtering device, meliorative, SUV calculator, magnetic pipe.